Alat Pendeteksi Dan Monitoring Kematangan Tape - Karina Djunaidi; Hendra Jatnika; Rahma Farah Ningrum; Wali Syahputro Cahoyo Kabidoyo (PETIR, 2019)
Cassava tape is a type of food made from the result of fermentation involving yeast in the manufacturing process. Detection of temperature, humidity and weight is carried out to observe the fermentation process in cassava into tape. The purpose of this study is to design a device that detects whether tape has reached the desired state automatically using the Dht11 sensor and load cell sensor, with the Arduino uno as the microcontroller. The result of this study showed that cassava tape which was fermented at 30-35 degrees Celsius in 24 hours was said to be in the perfect state and this was marked by the change in texture, aroma, color and taste of the cassava tape. So it can be concluded that tape fermentation using the detection device can improve the quality of the tape produced.